THE ROLE OF INTERNAL CONTROLS IN PREVENTING FINANCIAL MISMANAGEMENT IN NONPROFIT ORGANIZATIONS - Dr. Owa. Fredrick CNA; Dr. Onajite Alexandra Akpoveta Ololobou CNA; Onovayen Erus Evelyn (American Journals, 2024)
This paper provides a comprehensive exploration of the importance of internal controls within nonprofit organizations, focusing on their role in safeguarding financial integrity, ensuring accountability, and mitigating the risk of mismanagement. Drawing upon literature review, case studies, and best practices, the study highlights the challenges faced by nonprofits in implementing effective internal controls, including limited resources, volunteer dependence, and a complex regulatory environment. Building upon these insights, the paper offers a set of recommendations aimed at enhancing the effectiveness of internal controls within nonprofit organizations. These recommendations encompass areas such as investing in training and capacity building, leveraging technology solutions, strengthening oversight and governance, prioritizing risk management, engaging stakeholders, and fostering a culture of continuous improvement. By implementing these recommendations, nonprofits can strengthen their internal control frameworks, mitigate risks effectively, and uphold their commitments to accountability, transparency, and responsible stewardship of resources.
Keywords: Internal controls, financial mismanagement, Nonprofit organizations, Governance, Accountability and Risk management